A universal protocol for isolating retinal ON bipolar cells across species via fluorescence-activated cell sorting - Murenu, Elisa; Pavlou, Marina; Richter, Lisa; Rapti, Kleopatra; Just, Sabrina; Cehajic-Kapetanovic, Jasmina; Tafrishi, Neda; Hayes, Andrew; Scholey, Rachel; Lucas, Robert; Büning, Hildegard; Grimm, Dirk; et al. (Molecular therapy. Methods & clinical development, 2021)
Inherited retinal dystrophies (IRDs) are characterized by progressive degeneration and loss of light-sensing photoreceptors. The most promising therapeutic approach for IRDs is gene supplementation therapy using viral vectors, which requires the presence of viable photoreceptors at the time of intervention. At later disease stages, photoreceptors are lost and can no longer be rescued with this approach. For these patients, conferring light-sensing abilities to the remaining interneurons of the ON circuit (i.e., ON bipolar cells) using optogenetic tools poses an alternative treatment strategy. Such treatments, however, are hampered by the lack of efficient gene delivery tools targeting ON bipolar cells, which in turn rely on the effective isolation of these cells to facilitate tool development. Herein, we describe a method to selectively isolate ON bipolar cells via fluorescence-activated cell sorting (FACS), based on the expression of two intracellular markers. We show that the method is compatible with highly sensitive downstream analyses and suitable for the isolation of ON bipolar cells from healthy as well as degenerated mouse retinas. Moreover, we demonstrate that this approach works effectively using non-human primate (NHP) retinal tissue, thereby offering a reliable pipeline for universal screening strategies that do not require inter-species adaptations or transgenic animals.
Gesehen am 28.04.2021